The Effect of Torbangun Leaves Consumption on the Improvement of Breastmilk Volume in Post Partum Women in Ononamolo Village, Gunungsitoli City - Ade Ayu Prawita; Siti Ewin Pasaribu (Humanistic Network for Science and Technology (HNST), 2020)
Introduction: Insufficient volume of breastmilk production is the most common inhibiting factor leading to cessation of breastfeeding practice. This study aims to determine the effect of torbangun leaves (Coleus amboinicus lour) on the increase in breast milk volume in postpartum mothers in Ononamolo Village, Gunungsitoli Selatan District, Gunungsitoli City. Methods: The research design used a pre-experimental design with a pretest-posttest control group design. The population was post partum mothers in Ononamolo I Lot Village, Gunungsitoli Selatan District, Gunungsitoli City with a ratio of 1: 1. The sample size was 20 post partum mothers, selected using purposive sampling technique, with 1 intervention group given torbangun leaves for consumption for 14 consecutive days and 1 control group given booster milk to be consumed at the same time as the intervention group. The instrument used to measure milk production is to use a measuring cup. The results of data collection were analyzed by using the paired sample t-test. Results: Based on the research results obtained were the pre-test mean value of 6.10 with a standard deviation of 3.227, while in the post-test the average value was 10.95 with a standard deviation of 3.720. From the results of t-test with a confidence level of 95%, a p-value of 0.000 was obtained. Conclusion: There is an effect of the consumption of torbangun leaves on increasing the volume of breast milk in Ononamolo Village, Gunungsitoli Selatan District, Gunungsitoli City. Keywords: breastmilk volume production; torbangun leaves; post partum mothers